Convergence of communication and computing in future mobile communication systems - Yiqing ZHOU; Guojie LI (Dianxin kexue, 2018)
An overview and summary was provided on the convergence of communication and computing and the future research directions were clarified.As two key technologies of information science,communication and computing were born to be converged.In current mobile communication systems,from a single device or technique point of view,communication and computing had been well converged.However,to break the bottleneck of traditional mobile communication systems,it was necessary to converge communication and computing in a system level.Existing research demonstrates that a systematic convergence of communication and computing will reduce the channel capacity requirement on the mobile system and thus enhancing the system capability to support more services.Facing future mobile communication system,communication and computing convergence should be further studied in-depth from defining system service capabilities (basic theory),building a scalable,remodelable,transparent,modular system architecture and investigating service-aware cross-layer information exchange mechanisms,thus the sustainable development of mobile communication system could be promoted.